Characterization of basal-like subtype in a Danish consecutive primary breast cancer cohort. (2nd January 2018) - Kinalis, Savvas; Nielsen, Finn Cilius; Talman, Maj-Lis; Ejlertsen, Bent; Rossing, Maria
Abstract: Background: Transcriptome analysis enables classification of breast tumors into molecular subtypes. BRCA1/2 predisposed patients are more likely to suffer from a basal-like subtype and this group of patients displays a more distinct phenotype and genotype. Hence, in-depth characterization of this separate entity is needed. Material and methods: Molecular subtyping was performed on a consecutive and unselected series of 1560 tumors from patients with primary breast cancer. Tumors were classified by the 256 gene expression signature (CIT) and associated with basic clinical characteristics and aggregated expression levels in the hallmark gene sets. Results: Of the 1560 samples, 168 were classified basal-like and 120 patients were screened for BRCA1/2 mutations, resulting in 19 BRCA1/2 carriers, 95 non-carriers and six patients carried variants of unknown significance. The BRCA1/2 carriers were significantly younger and there were no carriers above 60 years of age. The tumors showed a loss in DNA-repair profile, as well as an upregulation in proliferative cancer signaling pathways. A robust molecular signature for identification of the BRCA1/2 - carriers was infeasible in the current cohort. Patients with a basal like breast cancer had the lowest median age and the largest median tumor size. They were almost exclusively diagnosed in disease stage III. Conclusions: Basal-like subtype is indeed a separate entity compared with other molecular breast cancer subtypes and the clinical course for this patient group should reflect the aggressiveness of this cancer. Taken together, patients being diagnosed with a basal-like breast cancer are in the youngest segment of breast cancer patients and are mainly diagnosed in stage III disease.